Technical and Vocational Education in China - Wu, Xueping (Springer Singapore, 2018)
This book provides comprehensive and up-to-date coverage of research on technical and vocational education in China. It discusses various aspects that range from such conventional topics as teaching at different levels, development history, regulations, policies, curriculum, specialty setup, teaching, faculty and management; to the status quo, transformation and current trends; as well as quantity expansion and quality improvement, all of which highlight the unique characteristics of technical and vocational education in China. This book is intended for researchers and graduate students, and will also help international readers to grasp the general situation regarding technical and vocational education in China. Combining rich content and a broad scope, the book will undoubtedly offer a valuable key to understanding China's technical and vocational education in the 21st century.